2021
DOI: 10.1186/s12885-021-08148-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between heavy metals and colon cancer: an ecological study based on geographical information systems in North-Eastern Iran

Abstract: Background Colorectal cancer has increased in Middle Eastern countries and exposure to environmental pollutants such as heavy metals has been implicated. However, data linking them to this disease are generally lacking. This study aimed to explore the spatial pattern of age-standardized incidence rate (ASR) of colon cancer and its potential association with the exposure level of the amount of heavy metals existing in rice produced in north-eastern Iran. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 55 publications
(21 reference statements)
0
27
0
Order By: Relevance
“…It provides a basis for health policymakers to determine priorities and distribute healthcare resources and decide intervention for disease prevention and control [ 14 ]. In cancer research field, studies have been performed to evaluate the association between environmental factors and cancer incidence based on spatial analysis [ 15 , 16 ]. These studies have reported the vulnerable areas for cancer incidence and suggested environmental factors that can be considered to resolve it by showing the inequality of cancer incidence and suggesting factors that can explain this imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…It provides a basis for health policymakers to determine priorities and distribute healthcare resources and decide intervention for disease prevention and control [ 14 ]. In cancer research field, studies have been performed to evaluate the association between environmental factors and cancer incidence based on spatial analysis [ 15 , 16 ]. These studies have reported the vulnerable areas for cancer incidence and suggested environmental factors that can be considered to resolve it by showing the inequality of cancer incidence and suggesting factors that can explain this imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple risk factors contribute to CRC development. This has been assessed in Iran previously [ 70 72 ] and among the various factors affecting CRC incidence, the main reason for early-onset CRC development might be the various germline mutations that have come to light in the last two decades [ 18 , 73 ]. Our study, in addition to demographic and pathological characteristics, addressed the MMR status of early-onset CRCs.…”
Section: Discussionmentioning
confidence: 99%
“…There are evidences between heavy metals pollution in environments and CRC in Iran as a good example. [ 23 29 ]…”
Section: Discussionmentioning
confidence: 99%